ANALISIS PUTUSAN PENGADILAN AGAMA TENTANG HAK HAḌONAH BAGI IBU MURTAD BERDASARKAN TINJAUAN MAQOSID SYARIAH - Akbar, Ali (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
This paper aims to find out Maqosid Syariah's review of haḍonah rights for apostate mothers as contained in the Maumere Religious Court Decision Number 1/Pdt.G/2013/Pa.Mur. This research is an empirical juridical research, where theresearcher examines the practice of law in the form of a decision by referring to legal norms and the basis of legal considerations regulated in the legislation. This research uses qualitative methods and is included in library research. This study describes the case of haonah rights for apostate mothers. In this decision, mothers who are prevented from getting haḍonah rights over their three children on the grounds that the harm to the child will be lighter if the child is in the care of the mother than in the care of the father who has been proven to have abandoned his family. It is clear that the parenting of the apostate mother (the respondent) will threaten the aqidah for the three children. if it is correlated with maqosid Syariah, the decision of haḍonah rights is given to apostates mother, which means that there is a need that must be maintained in a state of conflict (maintaining religion and soul). The Panel of Judges has prioritized hifz al-ddin (dhoruriyat and prioritized hifdz an-nafs (maintaining the soul) in order to consider the benefit and best interests of children.